A Triple Layer Model to Manage Romania's Health Risks and Educational Consequences - Paşcu-Gabără, Elena-Iuliana; Mihoreanu, Larisa (Journal of Economic Development, Environment and People, 2019)
This article explores the relationship between education and health from the perspective of revised literature and suggests an exercise combining the scientific theory with applied knowledge to achieve health progress reflected in health indices improvement for individuals and community. The relation between aggregate health condition, food and nutrition receives, through education, a new shape implying a three-way causality analysis to highlight the role of each entity exerting significant influences in the others’ good functioning. Three important issues are considered for the new and comprehensive definition: a) high level of education implies specific health benefits; b) health affects the level of education of the population; and c) living conditions, especially the childhood, affect both the population’s education and the aggregate health of the whole nation. This paper develops the new model to easier identify health risks, from the individuals’ attitude and their behavior in society, throughout life, within the institutional contexts. The conclusion shows that individuals and their personal traits are built, shaped and solidified within the first social frame (family), being permanently affected by surroundings. Subsequently, the influence of the community - through consolidation or disruptive factors - emphasized by political decisions, public establishments and their policies or other institutions – generates different social and cultural contexts whose aggregate consequences will be lasting and influence the national future.